Community integration and its relation to quality of life among poststroke patients/ Nurulhuda Jaafar and Padma A. Rahman - Jaafar, Nurulhuda; A. Rahman, Padma (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This study aims to identify the level of participation and activity after stroke (community integration), quality of life (QOL) and to determine whether there is any relationship between the level of participation and activity after stroke and QOL among post-stroke patients. This was a cross-sectional study by using Community Integration Questionnaires (CIQ) and Stroke Specific Quality of Life-12 (SSQOL-12). Participants were 21 men and 13 women attending rehabilitation treatment at National Association of Stroke Malaysia. Thirty four post-stroke patients with mean age of 64.5±12.0 years participated in this study. The mean CIQ and SSQOL-12 total scores were 11.9±4.8 and 40.2±5.8 respectively. The level of participation and activity among post-stroke patients was low in this study and QOL was found to be in moderate. A positive correlation was found between the level of participation and activity and QOL among them (r= 0.42, p< 0.05). Results of QOL and degree of participation in the community are the indicator of the successful stroke recovery. A low level of participation, indicating a need for occupational therapy (OT) to be more active in organizing support groups or community-based rehabilitation for post-stroke patients, otherwise, it will lead to worsening function and QOL.